The Syntax of Adverbials in Ewe-English Codeswitching - Evershed Kwasi Amuzu (Journal of cognitive science, 2016)
This paper discusses adverbial switches (single-word adverbs, adverb phrases, temporal noun phrases, prepositional phrases, and adverb clauses) in bilingual clauses in Ewe-English codeswitching, spoken in Ghana. The data analysed come mainly from two databases created in 1996 and 2002 respectively. It is found that while English adverbials occur in Ewe-based clauses, Ewe adverbials do not occur in English-based clauses. Furthermore, it is found that the English adverbials are allowed only in the four positions in which Ewe adverbials may occur. They do not occur in clause-medial adverb positions (e.g. the position in-between the subject-NP and the VP and in the VP-internal position) that are found in the English clause structure but not in the Ewe clause structure. The main significance of these findings is that although adverbial switches constitute an amorphous syntactic and semantic category, their distribution is consistent with principles outlined in Myers-Scotton’s Matrix Language Frame model that have been found attested in the distribution of English nouns, verbs, and adjectives in Ewe-English codeswitching (cf. Amuzu 1998, 2005a, 2014a, 2014b, 2015) and in codeswitching elsewhere in West Africa (Amuzu 2005b[2010], 2013a, Quarcoo 2009, Vanderpuije 2011, and Bolaji et al 2014). Also, the findings support other scholars’ studies of adverbial switches (e.g. Treffers-Daller 1994 and Hebblethwaite 2010) with respect to which of the languages in codeswitching contact may serve as the source of adverbial switches in bilingual clauses: the source is consistently the more socially dominant language, the embedded language from the perspective of the Matrix Language Frame model, in this case English. KCI Citation Count: 0